PENGEMBANGAN DAN SOSIALISASI PENGGUNAAN APLIKASI BERBASIS ZERO BASED BUDGETING UNTUK INDUSTRI SEKTOR PARIWISATA DAN HOSPITALITY - Sita Deliyana Firmialy; Cahyaningsih Cahyaningsih; Ismaya Adriyanti (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
The tourism and hospitality industry is a strategic sector that contributes significantly to regional economic growth. However, Micro, Small, and Medium Enterprises (MSMEs) in this sector still face substantial challenges in financial management, ranging from limited financial literacy and inefficient budget utilization to the lack of digital technology adoption. These issues result in low operational efficiency and weak business competitiveness. To address these challenges, this community service research developed an Android-based application by adopting the Zero-Based Budgeting (ZBB) and Zero Based Modeling (ZBM) approaches. Android was chosen as the initial development platform, as it is the most widely used and accessible system among MSMEs in Indonesia. The main features of the application include zero-based budgeting, daily transaction recording, automated financial reporting, budget utilization notifications, and educational modules on ZBB/ZBM concepts. The development process was carried out through a participatory approach in collaboration with MSME partners in Bandung Regency (West Java) and Luwu Regency (South Sulawesi). The research methodology combined the ZBB application development framework for the tourism sector, the systematic waterfall model, and the analysis–design–implementation principles in digital application development. Preliminary testing results indicate that the Android application successfully improves financial understanding, facilitates budget planning, and enables MSMEs to monitor cash flow in real time. Thus, the application functions not only as a financial recording tool but also as a digital learning medium that strengthens the sustainability and competitiveness of hospitality MSMEs in the era of digital transformation.